On affluence and poverty: morality, motivation and practice in a global age - Gabriel, I (2013)
This thesis looks at the failure of individual people living in affluent societies to do more to help those living in conditions of extreme poverty at the present moment. Affluent people have the capacity to assist, by contributing additional funds to aid and humanitarian organisations. Given an understanding of what is at stake, the fact that they fail to do so is both morally problematic and difficult to explain. Yet, without an understanding of the causes of inaction, it is difficult to know what measures may be taken to alleviate extreme suffering in the world today. The thesis draws upon different philosophical accounts of practical reason to argue that the conduct of the affluent can only be understood in one of three ways: these people may lack decisive reason to assist, they may be misinformed, or they may be rationally deficient in some regard. Considering each possibility in turn, it advances two central arguments. Firstly, the normative reasons claim is sound: affluent people, who do not incur minor costs by assisting, ought to do more. Secondly, these people tend to have false beliefs about the nature of poverty, to make substantive errors of judgement, and to follow flawed patterns of reasoning when they deliberate about what to do. Taken together, these factors explain their failure to act. Building upon this diagnosis, the thesis then considers how to respond to the problem of inaction, advancing a solution that is institutional in character. It argues for the construction of a division of labour between state and citizen, at the national level, which would see political institutions take on responsibility for poverty eradication, thereby leaving individuals freer to pursue their own personal goals and objectives. In order to perform this function effectively, wealthy nations would have to improve the quantity and quality of assistance that they provide to low-income countries. They would also have to cease partaking in practices that harm the global poor. This approach has a number of advantages over reliance on private philanthropy alone: it forms part of a fair and effective solution to the problem of motivating assistance, the arrangement it proposes is both stable and legitimate, and it is also something that could be achieved in practice. Therefore, it represents part of the best possible way in which to proceed.